Analisis Korelasi Pearson Total Unit Printed Circuit Board Assembly (PCBA) Good In Circuit Testing (ICT) - Puri Rahayu Nengsi; Andini Setyo Anggraeni; Widya Reza (Mathematical Sciences and Applications Journal, 2023)
Every job always faces challenges or problems from various aspects, one of the problems was related to PT PCI Elektronik Internasional's production target for In Circuit Testing (ICT), which aims to achieve 90% of the total ICT units as good product, it means that the minimum percentage of ICT units that must be good is 90% to achieve this target. However, not all units can be classified as 100% good. The quality of the ICT unit depends on the condition of the Printed Circuit Board Assembly (PCBA) and the testing machine. This research will analyze the relationship between the total PCBA good ICT units in May and June 2023 using correlation analysis. Based on the results of correlation analysis using the Pearson method, a correlation coefficient value of 0.843 was obtained between the total PCBA good ICT units in May 2023 and the total PCBA good ICT units in June 2023. The correlation value of 0.843 indicates that there is a strong positive linear relationship between the total PCBA good ICT units in May and June 2023.